New economics of inequality and redistribution - Bowles, Samuel (Federico Caff lectures, 2013)
"Economists warn that policies to level the economic playing field come with a hefty price tag. But this so-called 'equality-efficiency trade-off' - has proven difficult to document. The data suggest, instead, that the extraordinary levels of economic inequality now experienced in many economies are detrimental to the economy. Moreover, recent economic experiments and other evidence confirm that most citizens are committed to fairness and are willing to sacrifice to help those less fortunate than themselves. Incorporating the latest results from behavioral economics and the new microeconomics of credit and labor markets, Bowles shows that escalating economic disparity is not the unavoidable price of progress. Rather it is policy choice - often a very costly one. Here drawing on his experience both as a policy advisor and an academic economist, Samuel Bowles offers an alternative direction, a novel and optimistic account of a more just and better working economy"--